24. SPINAL ANESTHESIA FOR HIP SURGERY IN THE ELDERLY AT THONG NHAT HOSPITAL, HO CHI MINH CITY (Vietnam Journal of Community Medicine, 2024)
Background: The more medicine develops, the more surgical procedures are operated in the elderly, especially orthopedic surgeries of the lower limbs such as hip replacement, knee replacement. Spinal anesthesia has been linked to reduce risk of perioperative complications when compared with other methods.Purposes: To determine the effect of spinal anesthesia for hip replacement surgery and perioperative adverse events.Study methods: Case series.Results: The degree of motor and sensory block achieve a suitable condition for procedures (NRS
Keywords: Spinal anesthesia; Hip replacement; Elderly